Peran Guru Tahsin dalam Penerapan Metode Ummi untuk Meningkatkan Kualitas Membaca Al-Qur’an pada Peserta Didik MI Plus Al Bahroin Padangan - Tirta Puja Astuti; Maulida Fikria Nashol; Ni'matus Sa'adah, Ulfa (Al Fattah Ejournal Sma Al Muhammad Cepu, 2024)
The Ummi method of Al-Qur’an at MI Plus Al Bahroin Padangan is interesting because not all schools apply this method. The purpose of this study was to describe the application of the Ummi Method of Al-Qur'an learning to students at MI Plus Al Bahroin Padangan and to analyze the results of applying the Ummi Method of AlQur'an learning to students at MI Plus Al Bahroin Padangan. If the implementation is going well, the quality of the student's reading is following the applicable tajwid laws, and the implementation of learning is by the directions of the Ummi Foundation. The problem that arises is, currently there is a shortage of classes for learning activities because there is a construction of a new class building so there is a reshuffling of places such as the library, office, kitchen, and so on. So several groups study at the school mosque. This makes it less conducive. The quality of the teachers is good because there are 9 teachers and only 2 are not certified.  This type of research is descriptive qualitative. Data collection techniques used are observation, interviews, and documentation. There were 4 sources of informants, namely 1 Al-Qur'an teacher coordinator, the head of the madrasah, and 2 students of class IV. Determination of information using a purposive sampling technique. Data analysis used is data reduction and verification. As well as the validity of the data in research using source triangulation. The results of this study found that 1) The Ummi Al-Qur'an learning method application at MI Plus Al Bahroin had gone well. The implementation of learning has been implemented following the Ummi Foundation system standards. 2) The results of applying the Ummi method at MI Plus Al Bahroin went well according to the Ummi Foundation's directions and guidelines. The supporting factors for learning the Ummi method include schools that have registered MoUs with regional Ummi, foundations, and school principals who fully support learning the Qur'an for the Ummi method, complete learning facilities/media, certified teachers, and parental support. While the inhibiting factors include: the lack of a place to teach Ummi, the condition of the students, and the condition of the teacher.